Autophagy Activation and Protection From Mitochondrial Dysfunction in Human Chondrocytes. Issue 4 (April 2015) - López de Figueroa, Paloma; Lotz, Martin K.; Blanco, Francisco J.; Caramés, Beatriz
Abstract : Objective: Autophagy is a key pathway of cellular homeostasis for removing damaged macromolecules and organelles, including mitochondria. Recent studies indicate that activation of autophagy is defective in aging and osteoarthritis (OA), contributing to cell death and tissue damage. In addition, there is increasing evidence that mitochondrial dysfunction plays an important role in OA pathogenesis. The objective of this study was to determine whether activation of autophagy protects against mitochondrial dysfunction in human chondrocytes. Methods: Human chondrocytes were treated with oligomycin, an inhibitor of mitochondrial respiratory chain complex V. Autophagy activation was analyzed by determination of light chain 3 membrane‐bound form II (LC3‐II), a marker of autophagosome formation. To investigate whether autophagy protects from mitochondrial dysfunction, autophagy was induced by rapamycin, the selective inhibitor of mammalian target of rapamycin complex 1 (mTORC‐1), and by torin 1, the inhibitor of mTORC‐1 and mTORC‐2. Small interfering autophagy‐related 5 was used to evaluate the role of autophagy in mitochondrial dysfunction. Results: Mitochondrial dysfunction was induced by treatment with oligomycin, which significantly decreased mitochondrial membrane potential (ΔΨm). This was associated with increased production of reactive oxygen species and cell death. Autophagy activation, as reflected by LC3‐II, was decreased in a time‐dependent manner. To evaluate whether autophagy regulates mitochondrial function, chondrocytes were pretreated with rapamycin and torin 1 before oligomycin. Autophagy activation significantly protected against mitochondrial dysfunction. Conversely, genetic inhibition of autophagy induced significant mitochondrial function defects. Conclusion: Our data highlight the role of autophagy as a critical protective mechanism against mitochondrial dysfunction. Pharmacologic interventions that enhance autophagy may have chondroprotective activity in cartilage degenerative processes such as OA.